Modelos familiares y vejez en España. Siglos XVIII a XX - Mikelarena Peña, Fernando; Pérez-Fuentes Hernández, Pilar (El Colegio de México A.C., 2001)
The article begins with an attempt to prove whether a relationship existed between the plurality of family types in Spanish and greater or lesser longevity. By linking indicators concerning the complexity of households and the longevity of the population, drawn from the 1860 census, the authors prove that the diversity of family types fails to explain longevity. It then explores a range of historical situations in which it analyzes how old age was dealt with in Spain in relation to the various family types. In rural areas, old age was experienced very differently according to the predominant family type. Thus, in the province of Cuenca, from the 17th to the 20th century, old age meant loneliness, whereas in 18th century Navarra, the elderly lived mainly in complex households. Urban spaces provide a range of situations in which the dominant family type loses its explanatory capacity, giving way to other factors such as immigrations, the dynamics of the labor market, marriage patterns and above all, the levels of those who never marry, and gender roles. In 18th century Pamplona, a city where the stem family model predominated, the elderly lived in complex households, although to a lesser extent than those in adjacent rural areas. The case of Bilbao, an economic center in northern Spain with a predominance of simple households, shows how solidarity with the elderly can also be compatible with this family type. The belief that, in industrial cities, the elderly lived in solitary households contrasts with the high number of elderly living in complex and even nuclear households. Finally, San Salvador del Valle shows the effect that rapid industrialization, coupled with largescale male immigration, had on old age, as well as the subsequent capacity for adaptation shown by nuclear families in incorporating the elderly into complex households. Despite the variety of family types that existed in Spain throughout the 18th and 20th centuries, this did not affect people's longevity or patterns of solidarity with the elderly; on the contrary, solidarity constitutes one of the features of familial culture throughout the country.